Post-renal transplantation Polyomavirus infection: A case report - Costa, Kellen Micheline Alves Henrique; Almeida, José Bruno de; Félix, Ricardo Humberto de Miranda; Silva Júnior, Maurício Ferreira da; Franco, Marcelo Fabiano de (Brazilian Journal of Transplantation, 2010)
Polyomavirus nephropathy (BKV) occurs in 1.1% to 9.3% of kidney transplant recipients, causing graft loss in more than 40% of cases. The primary infection occurs in the childhood, and the virus remains latent into the organism, becoming reactive under immunosuppressant conditions. We report a 45-year-old woman case recipient of a renal allograft three years ago, who was in chronic use of tacrolimus and mycophenolate mofetil, and presented progressive loss of renal function during a diarrheic episode despite the adequate treatment. Graft biopsy revealed the presence of cells with polyomavirus inclusions, being initiated sirolimus and human immunoglobulin. With the instituted therapeutic the renal function improved, and a new biopsy performed after hospital internment did not show histological alterations by polyomavirus.